PENGARUH MEKANISME CORPORATE GOVERNANCE, UKURAN PERUSAHAAN, LEVERAGE DAN KUALITAS AUDIT TERHADAP INTEGRITAS LAPORAN KEUANGAN (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI Periode Tahun 2014-2016) - Riris Ning Pambudi Untari, 14.05.62.0030; Maryono, Maryono (Students' Journal of Accounting and Banking, 2018)
The purpose of this research is to influence Corporate Governance Mechanism, Company Size, Leverage And Audit Quality To Integrity Of Financial Statement at Manufacturing Company Listed on BEI Period Year 2014-2016. Sampling technique using purposive sampling. The sample criteria in this study are manufacturing companies listed on the Indonesia Stock Exchange (BEI); The Company uses Rupiah currency; The company has a positive profit and the manufacturing company has complete data according to the variables needed in the study. Analyzer used is multiple linear regression. The results of the analysis can be concluded that: Institutional ownership has no effect on the integrity of financial statements. Managerial ownership has no effect on the integrity of financial statements. The audit committee has no effect on the integrity of the financial statements. Independent commissioners have a positive influence on the integrity of financial statements. The size of the company has a significant positive effect on the integrity of the financial statements. Leverage does not affect the integrity of the financial statements. Audit quality positively affects the integrity of financial statementsKeywords: Corporate Governance Mechanism, Company Size, Leverage And Audit Quality To Financial Statement Integrity